Co-delivery of insulin-like growth factor 1 receptor specific siRNA and doxorubicin using chitosan-based nanoparticles enhanced anticancer efficacy in A549 lung cancer cell line. (17th February 2018) - Shali, Hajar; Shabani, Mahdi; Pourgholi, Fatemeh; Hajivalili, Mahsa; Aghebati-Maleki, Leili; Jadidi-Niaragh, Farhad; Baradaran, Behzad; Movassaghpour Akbari, Ali Akbar; Younesi, Vahid; Yousefi, Mehdi
Abstract: Here, we investigated the effects of dual delivery of IGF-1R siRNA and doxorubicin by chitosan nanoparticles on viability of A549 lung cancer cells line by utilization of MTT and qRT-PCR. Furthermore apoptosis and migration of treated cells were assessed by Annexin-PI and wound healing assays, respectively. The chitosan nanoparticles had about 176 nm size with zeta potential and polydispersive index about 11 mV and 0.3, respectively. The IGF-1R siRNA had synergistic effect on DOX-induced cytotoxicity and apoptosis in tumour cells. In addition, siRNA/DOX-loaded chitosan nanoparticles could significantly decrease migration and expressions of mmp9, VEGF and STAT3 in A549 cells.